2020
DOI: 10.1007/s10554-020-01911-8
|View full text |Cite|
|
Sign up to set email alerts
|

Dual-energy CT angiography in suspected pulmonary embolism: influence of injection protocols on image quality and perfused blood volume

Abstract: To compare intravenous contrast material (CM) injection protocols for dual-energy CT pulmonary angiography (CTPA) in patients with suspected acute pulmonary embolism with regard to image quality and pulmonary perfused blood volume (PBV) values. A total of 198 studies performed with four CM injection protocols varying in CM volume and iodine delivery rates (IDR) were retrospectively included: (A) 60 ml at 5 ml/s (IDR = 1.75gI/s), (B) 50 ml at 5 ml/s (IDR = 1.75gI/s), (C) 50 ml at 4 ml/s (IDR = 1.40gI/s), (D) 40… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 39 publications
0
7
0
Order By: Relevance
“…Before each scan, a predefined amount of iodinated contrast medium was applied (Imeron® 350, Bracco) via an antecubital vein using an automated injector. In the EID group, 50 mL of contrast medium was administered with a flow rate of 4 mL/s, corresponding to an iodine delivery rate of 1400 mg/s [ 14 , 15 ]. Based on recent studies discussing a potential for contrast medium dose savings in PCD-CT by up to 50% while still obtaining diagnostic attenuation [ 13 , 16 ], we aimed for a significant reduction in terms of halving the dose of our standard dual-energy acquisition protocol.…”
Section: Methodsmentioning
confidence: 99%
“…Before each scan, a predefined amount of iodinated contrast medium was applied (Imeron® 350, Bracco) via an antecubital vein using an automated injector. In the EID group, 50 mL of contrast medium was administered with a flow rate of 4 mL/s, corresponding to an iodine delivery rate of 1400 mg/s [ 14 , 15 ]. Based on recent studies discussing a potential for contrast medium dose savings in PCD-CT by up to 50% while still obtaining diagnostic attenuation [ 13 , 16 ], we aimed for a significant reduction in terms of halving the dose of our standard dual-energy acquisition protocol.…”
Section: Methodsmentioning
confidence: 99%
“…Owing to improvements in detector sensitivity and the enhanced spectral separation of newer DECT scanners, it is also possible to scan without injecting a saline chaser. Injection rates of 40 mL and below with 3 mL/s were considered insufficient for good-quality iodine maps, whereas a higher amount of contrast medium was associated with a higher quality of iodine maps [ 38 ]. Bacon et al reported a total volume of up to 100 mL (300 mg iodine/mL) [ 39 ].…”
Section: Postprocessingmentioning
confidence: 99%
“…Bacon et al reported a total volume of up to 100 mL (300 mg iodine/mL) [ 39 ]. In the literature, the delay varies from 7 to 12–15 s [ 38 , 40 , 41 ], and triggering thresholds are recommended to be 100–120 HU [ 38 , 39 ]. Considering the inter-individual differences between the patients and scanning hardware, these protocols should be an orientation for creating an ideal protocol for each site and radiographer using their experience.…”
Section: Postprocessingmentioning
confidence: 99%
See 1 more Smart Citation
“…Computed tomography pulmonary angiography (CTPA), owing to its high sensitivity and specificity as well as wide availability, represents the imaging modality of choice for the diagnosis or exclusion of pulmonary embolism [ 5 , 11 , 12 ]. The scan initiation of CTPA is usually performed with the bolus tracking technique which enables an individualized optimization of the scan start in relation to the contrast arrival in the pulmonary artery circulation [ 13 , 14 ]. Still, there are numerous factors affecting the timing of contrast enhancement in CTPA which are not being taken into account entirely with bolus tracking.…”
Section: Introductionmentioning
confidence: 99%